Vital directions for mathematics education research - Leatham, Keith R. (Springer New York, 2013)
What are the most important questions researchers in Mathematics Education should be trying to answer?   What opportunities and challenges face the Mathematics Education community as we seek to answer them?  In this book, some of the most well-respected researchers in the field of Mathematics Education answer these and other questions and lay forth their visions of the vital directions research should take in the coming decades. Each of the international authors provides a compelling take on critical issues related to improving mathematics teaching and learning. Chapters provide an excellent background on current areas of research, furnishing reasoned rationales for conducting research on particular problems and providing compelling arguments that invite us to rethink our assumptions and priorities.